Minat Belajar Siswa Pada Pembelajaran Matematika Integrasi Nilai-Nilai Islam - Pebria, Windi; Imamuddin, M.; Isnaniah, Isnaniah; Ismirawati, Ismirawati (Tadris Matematika, 2024)
Students' interest in learning mathematics is needed to achieve better learning goals. If students' interest in learning is low, it can cause a less effective learning process carried out by the teacher. This study aims to describe students' interest in learning mathematics Integration of Islamic values. The method used in the research is descriptive quantitative method. The instrument used is a questionnaire with scoring using a Likert scale. The sample in this study were students of class VIII H SMP Negeri 1 Bukittinggi totaling 29 students. The results showed that in general, students' interest in learning mathematics in mathematics learning integrated with Islamic values was in the high category, where the average score was 78. A total of 138% or 4 students has an interest in integrated mathematics learning with Islamic values with moderate criteria, and 86.2% or 25 students have an interest in integrated mathematics learning with Islamic values with high criteria. Students' interest in learning mathematics determines whether mathematics learning is effective by using learning combined with Islamic values by the teacher.